Impact of Fintech on Financial Performance of MSMES in Bali with Financial Literacy as Moderator - Ica Rika Candraningrat; Vera Intanie Dewi; Putu Ayu Kezia Dewi (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2025)
This study examines the impact of fintech on the financial performance of micro, small, and medium enterprises (MSMEs) in Bali, with financial literacy as a moderating variable. A quantitative approach was employed, utilizing primary data collected through questionnaire distribution. The sampling method used was purposive sampling, with a total of 150 respondents. The findings indicate that fintech has a positive and significant effect on financial performance. Furthermore, financial literacy positively moderates this relationship, strengthening the impact of fintech on financial performance. These results align with the Theory of Planned Behavior and the Theory of Financial Innovation. The higher the financial literacy of MSME owners, the more effectively they utilize fintech to enhance financial performance. Keywords : Fintech; Financial Performance; Financial Literacy; MSMEs